(untitled) (Research, Society and Development, 2022)
The objective of this review is to provide the national history of monitoring of the Program on Pesticide Residue Analysis in Food (PARA), as well as to analyze the publications referring to the data released by PARA. This is an integrative review guided by the questions: “What is the historical evolution of the execution of PARA?” and “What results related to the Program have been disclosed?” Program reports corresponding to the period from 2001 to 2020 were consulted. The search for articles was carried out in PubMed and Scielo and in Theses and Dissertations, in the Capes Online Catalog. A combination of the descriptors ’pesticides’, ’ residues’, ’food’ and ’Brazil’ and the corresponding ones in English was used. All PARA reports available on the Anvisa website were analyzed. Articles and Dissertations/Theses were pre-selected by titles, followed by readings of abstracts and later in full. The studies highlight the foods that presented the most pesticide residues above the Maximum Residue Level (MRL), prohibited pesticides for the culture and presence of multi-residues. Since the implementation of PARA in 2001, until 2019, more than 50% of the monitored foods contained the presence of pesticide residues. Over the years, the Program has increased the types of foods and active ingredients of pesticides evaluated. However, what draws more attention is the presence of unauthorized pesticides for crops and the growing increase in residues above the MRL in food, results published by the Program and related studies, raising awareness of possible negative impacts on the health of the population.